A new species of Clidicus in East Malaysia (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
A new species of Clidicini ant-like stone beetles, Clidicus mawarensis sp. n., is described and illustrated. The holotype male was collected in East Malaysia (Borneo: Sabah); the new species belongs to a group of large-bodied Clidicus, and shows similarities to C. ganglbaueri Reitter; the male has unusually complex structures of the aedeagal apical region.